(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2020)
The emission that caused by fossil fuel and the constantly increasing pollution rates made the engineers and researchers focus on using hydrogen as a fuel instead of fossil fuel. Fuel cells are one of the technologies that are widely explored all over the world. Fuel cell vehicles are environmentally friendly and use hydrogen as fuel and generate zero emissions. Optimization strategies is the best way for identify the best solution to the design problem. In this paper we will use particle swarm optimization and genetic algorithm to optimize the obtained model. The result show that case 5 is the best solution after optimization in this case the fuel consumption was 2.7668